2018
DOI: 10.1136/bmjqs-2018-008418
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired and hospital-acquired medication harm among older inpatients and impact of a state-wide medication management intervention

Abstract: BackgroundWe previously reported reduction in the rate of hospitalisations with medication harm among older adults with our ‘Pharm2Pharm’ intervention, a pharmacist-led care transition and care coordination model focused on best practices in medication management. The objectives of the current study are to determine the extent to which medication harm among older inpatients is ‘community acquired’ versus ‘hospital acquired’ and to assess the effectiveness of the Pharm2Pharm model with each type.MethodsAfter a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Finally, our study was limited to the immediate 45-day post-hospital discharge period, while ongoing efforts by community pharmacists working with patients up to a year postdischarge may be beneficial in reducing medication harm. 34,35…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, our study was limited to the immediate 45-day post-hospital discharge period, while ongoing efforts by community pharmacists working with patients up to a year postdischarge may be beneficial in reducing medication harm. 34,35…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The intervention generated an estimated savings of $6.6 million per year in avoided hospitalisations compared with $1.8 million in annualised costs to deliver the intervention. With the study reported in this issue of BMJ Quality and Safety , the authors extend these results by delving more deeply into the findings, evaluating in what settings adverse drug events were reduced and which medications accounted for the greatest reduction 13. Overall, 70% of medication harms were present on admission (ie, presumably developed in the community), with the remaining 30% being hospital-acquired (ie, identified during the hospital stay but not recorded as present at the time of admission).…”
mentioning
confidence: 90%
“…Into this breach step Pellegrin et al with the Pharm2Pharm intervention, outcomes of which are reported in this issue of BMJ Quality and Safety 13. In the Pharm2Pharm programme, hospital-based pharmacists identified inpatients at high risk of medication misadventures, using criteria such as use of multiple medications, presence of high-risk medications such as warfarin or glucose-lowering drugs and history of previous acute care use resulting from medication-related problems 14.…”
mentioning
confidence: 99%
“…Medication management reflects a process in which medications are selected, procured, delivered, prescribed, reviewed, administered and monitored to assure high-quality patient care, 1 which has been evidenced as a strategy to address patient safety challenges related to medication errors. 2 This approach is essentially multidisciplinary and typically involves a range of healthcare clinicians including pharmacists, nurses and physicians. 3 Medication safety is the process and the product of medication management and relies heavily on a strong safety culture.…”
Section: Introductionmentioning
confidence: 99%